Designing Standard Operating Procedure in Beauty Salon Using Knowledge Conversion Model (Case Study: Bunda Umar Muslimah Salon) (The Indonesian Journal of Business Administration, 2021)
Caring for self-beauty in a salon has become necessary for most women. One of factor determines in choosing a beauty salon is the service quality. Bunda Umar Salon is a Muslim woman-only beauty salon that always committed to provide quality service. However, some customers still complain about the disappointing service. The absence of written SOPs has resulted in the Bunda Umar Salon being unable to meet acceptable service standards. This study aims to design SOPs of Bunda Umar Salon and its implementation plan.The research uses observations and literature reviews to determine the most appropriate method in designing Bunda Umar Salon's SOPs. The SOPs design begins with determining the service critical points. A knowledge conversion process then be carried out based on Nonaka's SECI (Socialization, Externalization, Combination, and Internalization) Model to convert tacit knowledge into explicit knowledge. The acquired knowledge is then compiled into a written SOP format and then got tested. The SOP implementation plan is made with a strategy to address employee resistance to change, which found during the trial. The SOPs make it easier for employees to understand the work flow and increase their discipline. Employees who perform according to the SOPs provide satisfying service for customers. Keywords: beauty salon service, employee resistance to change, knowledge conversion, NONAKA’s SECI model, standard operating procedure (SOP).